A lost generation? The impact of the COVID‐19 pandemic on early career ASD researchers. Issue 6 (24th March 2021) - Harrop, Clare; Bal, Vanessa; Carpenter, Kimberly; Halladay, Alycia
Abstract: The COVID‐19 pandemic has disrupted autism research and services. Early career researchers (ECRs) are particularly vulnerable to the impact of the pandemic on job security and career development. The goal of this study was to capture the challenges ECRs are facing during the pandemic and the supports that are needed for career development and research. ECRs were invited to complete an online survey that focused on four major areas; the impact of COVID‐19 on their research; changes in productivity due to COVID‐19; changes to training due to COVID‐19; and current mental health. 150 ECRs were eligible and provided sufficient data for inclusion. All but one ECRs reported their research had been negatively impacted by the pandemic. Reductions in productivity were reported by 85% of ECRs. The biggest impacts included recruitment of participants, increased needs at home and personal mental health. ECRs reported a 3‐fold increase in burnout, as well as increased anxiety. ECR supports, such as funding, flexibility, and tenure extensions, are required to ensure ASD research does not suffer from a "lost generation" of researchers. Lay Summary: The COVID‐19 pandemic has had negative impacts on research around the world. Loss of productivity impedes autism research discoveries. However, researchers in the earliest phases of their career, specifically postdoctoral fellows through individuals in assistant professor (or equivalent) positions, are particularly vulnerable to long‐lasting effects of pandemic‐related disruptions which may limit their ability to continue as autism researchers. This survey highlights the needs of this group and identifies mechanisms by which these early career researchers may be supported in this time. This is critical to ensure the next generation of ASD researchers and clinician scientists continue on the path to advancing understanding of autism in the decades to come.